2016
DOI: 10.1158/0008-5472.can-15-1519
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Antagonist of the β-Catenin/TCF4 Interaction Blocks the Self-Renewal of Cancer Stem Cells and Suppresses Tumorigenesis

Abstract: Wnt/b-catenin signaling is a highly conserved pathway essential for embryogenesis and tissue homeostasis. However, deregulation of this pathway can initiate and promote human malignancies, especially of the colon and head and neck. Therefore, Wnt/b-catenin signaling represents an attractive target for cancer therapy. We performed high-throughput screening using AlphaScreen and ELISA techniques to identify small molecules that disrupt the critical interaction between b-catenin and the transcription factor TCF4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 53 publications
1
119
0
Order By: Relevance
“…Of these binding factors, the transcription of the CDH1 , LEF1 and TCF7L2 genes was up-regulated in GC cells (Table 1). It has been reported that a small molecule antagonist of the β-catenin/T-cell transcription factor 4 [TCF4; official name is transcription factor 7 like 2 (TCF7L2)] interaction inhibits self-renewal of CSCs and suppresses tumorigenesis[19]. The 3D complex structures of β-catenin and TCF7L2 are available[20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Of these binding factors, the transcription of the CDH1 , LEF1 and TCF7L2 genes was up-regulated in GC cells (Table 1). It has been reported that a small molecule antagonist of the β-catenin/T-cell transcription factor 4 [TCF4; official name is transcription factor 7 like 2 (TCF7L2)] interaction inhibits self-renewal of CSCs and suppresses tumorigenesis[19]. The 3D complex structures of β-catenin and TCF7L2 are available[20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SW620 spheroids exhibited increased expression of β-catenin compared to monolayers cells suggesting that TG2 and β-catenin may be necessary in cancer stem cell formation [50]. More recent studies also suggest that the self-renewal capacity of cancer stem cells in colon and head and neck cancer cells was blocked by perturbation of the interaction between β-catenin and the transcription factor TCF4 in the nucleus [52]. This supports our current notion in SW620 cells where TG2 plays a role in inhibiting β-catenin ubiquitination and thus facilitates accumulation of β-catenin in the nucleus where it can interact with TCF4, enhancing the self-renewal and enhancing cancer stem cell capacity, a process that can be perturbed by inhibiting TG2.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assays were performed using MTT solution (Sigma-Aldrich) and processed according to the manufacturer’s instructions and Stat Fax 2100 ELISA reader. Colony and sphere formation were performed similar to that described in Staller et al (2001) and Fang et al (2016).…”
Section: Methodsmentioning
confidence: 99%